First Report of Echinococcus ortleppi in Free-Living Wild Boar (Sus scrofa) from Portugal - Mateus, Teresa Letra (2021)
Cystic echinococcosis (CE) is a zoonosis that is prevalent worldwide. It is considered endemic in Portugal but few studies have been performed on Echinococcus granulosus sensu lato and their hosts. In this study, CE cysts are reported for the first time in a free-living wild boar (Sus scrofa) in Portugal. The presence of the metacestodes in the liver of the wild boar was identified by morphological features, microscopic examination and molecular analysis. The sequencing of part of the DNA nuclear ribosomal internal transcribed spacer-1 (ITS-1) region revealed a G5 genotype that presently corresponds to Echinococcus ortleppi. This is the first report of E. ortleppi in Portugal and to the best of the authors’ knowledge, in Europe. These results suggest that wild boar may be a host of CE, namely, crossing the livestock–wildlife interface, which has important public health implications. Wildlife reservoirs must be taken into account as CE hosts and surveillance of game as well as health education for hunters should be implemented using a One Health approach, with implementation of feasible and tailor-made control strategies, namely, proper elimination of byproducts in the field.